Urban parks are a refuge for birds in park-poor areas - Vasquez, Amy V.; Wood, Eric M. (Frontiers in Ecology and Evolution, 2022)
Urban parks provide amenities that support both human and animal communities. However, parks are often unevenly distributed within cities. One metric used to assess the distribution of parks to the public is termed the Park Score. The Park Score is an approach to measure access, acreage, investment, and amenities, and is designed to understand a city’s needs for greenspace, with a major focus on public health. In addition to issues related to public health, a disparity in the distribution of urban parks may pose a barrier for wildlife, such as birds. Yet, this remains unclear. We designed a study to quantify the role of parks in providing a refuge for birds across a park-needs gradient in Greater Los Angeles (L.A.) — a metropolis with one of the lowest park scores in the U.S. We had two objectives to address our goal. First, we quantified patterns in habitat features and avian communities within and adjacent to parks. Second, we analyzed relationships among habitat features within and adjacent to parks on avian abundance. We sampled birds and habitat features at 48 parks across a park-needs gradient in L.A. from October to March of 2017/18 and 2018/19. We found three lines of evidence supporting the refugia effect of parks. First, habitat features within parks were similar between low- and high-needs areas of L.A, and this likely influenced avian abundance patterns, which were also alike. Second, avian communities were generally similar across the park-needs gradient, where parks in high-needs areas harbored birds affiliated with forest and shrub ecosystems. Third, bird abundance patterns were related to numerous habitat features within parks, regardless of where parks occurred in the city. The patterns we uncovered were opposite to what is found in residential areas (i.e., luxury effect), suggesting that parks provide important habitat for birds, whether in high- or low-needs sections of L.A. Our results stress the role of parks as refugia in park-poor areas because they provide habitat in otherwise inhospitable urban conditions. Continued investment in park development in high-needs areas can thus potentially be a win-win when considering the benefits to people and birds.